The sexual behaviour of Panstrongylus megistus (Hemiptera: Reduviidae): an experimental study - Herton Helder Rocha Pires; Marcelo Gustavo Lorenzo; Claudio Ricardo Lazzari; Liléia Diotaiuti; Gabriel Manrique (Memorias do Instituto Oswaldo Cruz, 2004)
The factors affecting the sexual behaviour of Panstrongylus megistus were studied under laboratory conditions. A general description of mating behaviour is presented for this species. The effect of the time elapsed after the first imaginal feeding on the mating frequency, the motivation of males to mate and the rejection behaviour by females, were analyzed. We also determined the number of copulas accepted by females of this species. Finally, the possible existence of a sexual chemical signal promoting male aggregation around mating couples was evaluated. Results showed that mating frequency increased with the time elapsed since the first adult meal. Despite the number of male copulatory attempts did not change as a function of time, the rejection behaviour of females became gradually less frequent. Females rejected mating by means of body flattening on the substrate, abdominal movements, evasion or stridulation. After a single copula, females did not usually accept to mate again. Neither male nor female aggregation around mating couples was observed, suggesting the absence of a sexual assembling pheromone in P. megistus.